Complications of Post-Partum Intrauterine Contraceptive Device Insertion - Ayesha Ashraf, Usman Bari, Shahrukh Khan, Mohammad Mohsin Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the complications of post-partum intrauterine contraceptive device insertions in terms of frequency of bleeding and expulsion. Patients and Methods: A total number of 180 females aged 18–40 years with gestational age 36–40 weeks and having Hb ≥8 g/dl at time of delivery. All antenatal patients admitted for delivery to our hospital were counseled for PPIUCD. The PPIUCD was inserted within 10 minutes after placental delivery. Patients were called for follow-up after 6 weeks, 3 months and 4 months. Complications of PPIUCD were measured in terms of bleeding and expulsion rate within 4 months of follow-up. Results: Mean age of patients was 28.86±4.83 years. Mean parity of females was 2.13±0.90. There were 126 (70.0%) patients who underwent normal vaginal delivery while remaining 54 (30.0%) patients underwent C-section. At the end of follow-up period, bleeding was found in 26 (14.4%) patients after IUCD insertion and expulsion was found in only 11 (6.11%) patients. Conclusion: Post-partum insertion of intra-uterine contraceptive device (IUCD) is associated with acceptable rates of complications. In present study bleeding occurred in 15.27% patients and expulsion occurred in 6.89% patients after post-partum insertion of IUCD